Labour internationalism in the global south the SIGTUR initiative - O'Brien, Robert 1963- (Cambridge University Press, 2019)
An analysis of labour internationalism that explores in depth the experience of the Southern Initiative on Globalisation and Trade Union Rights (SIGTUR)
Keywords: SIGTUR; Globalization; International organization; Labor movement-Developing countries; Labor unions-Developing countries; Internationalisierung; Globalisierung; Gewerkschaftsbewegung; Solidarität; Schwellenländer; BUSINESS & ECONOMICS / Labor; POLITICAL SCIENCE / Labor & Industrial Relations